East Asian democratization : impact of globalization, culture, and economy - Compton, Robert W., 1964- (Praeger, 2000)
This text creates an Asian political development model to take into account cultural and historical perspectives. This model is then tested with quantitative indicators and through a series of case studies, based on Japan, South Korea and Thailand.